American Dreams Represented through the Color in Fitzgerald’s The Great Gatsby - Ghiotto, Monica Federica; Wijanarka, Hirmawan (Journal of Language and Literature, 2016)
This article aims at observing F. Scott Fitzgeraldâ€™s The Great Gatsby that was first published in 1925, a novel about a man named Gatsby who wants to get his love back by making effort to be a rich person. The prominent color symbols and how the symbols represent the American Dream are the main concern of this article. Two objectives are set to guide the study of the novel. The first is to explai the color symbols that are prominent in the study, and the second is to analyze how the color symbols represent the American Dream. From the analysis, there are three prominent colors presented in the novel: green, white and gold. Green that symbolizes the American Dream of the better life and happiness can be seein in the green light, the green leather conservatory, the green-house, the apple-green shirts, the green jersey, the green card, the green Sound, and the green breast of the new world. White symbolizes the American Dream of of fame, wealth, perfection, innocence, and success. This color can be seen in the white palaces of fashionable East Egg, the white dress, the white windows, the white roadster, the white cards, and the white flannel suits. Gold that symbolizes the American Dream of material prosperity can be seen in the golden arm, the golden shoulder, the gold-colored tie, and the toilet set of pure dull gold color.Â